The impact of dietary supplementation of Quercetagetin on growth, antioxidant capacity, and gut microbiota of diquat-challenged broilers - Yang, Shuo; Huo, Min; Su, Zixuan; Wang, Fangfang; Zhang, Yongying; Zhong, Cuihong; Shi, Yuxiang (Frontiers in Microbiology, 2024)
This experiment aimed to investigate the effects of Quercetagetin (QG) on the growth performance, antioxidant capacity, and cecal microbiota of broilers. Two hundred and forty 21-day-old WOD168 broilers with similar body weights were randomly divided into five groups of six replicates each with eight chickens. The control group was fed a basal diet composed of corn and soybean meal, while the experimental groups received basal diets supplemented with 0, 10, 20, and 40 mg/kg QG, along with intraperitoneal injection of 20 mg/kg body weight Diquat (DQ). The experiment lasted for 21 days.The results showed that: 1) QG significantly alleviated the decrease in average daily feed intake and average daily gain induced by Diquat, reduced the elevation of serum ACTH content, and significantly increased GH content (P<0.05); 2) QG supplementation significantly mitigated the decrease in serum CAT activity and duodenal GSH-Px activity induced by Diquat (P<0.05), as well as the increase in MDA content (P<0.05); additionally, QG significantly increased the gene expression levels of GSH-Px, Nrf2, and Keap1 (P<0.05); 3) Alpha and Beta diversity analysis revealed that QG supplementation significantly increased the cecal microbial OTUs and Chao1 index of broilers (P<0.05). At the phylum level, compared with the Diquat group, the LQG group significantly decreased the relative abundance of Firmicutes (P<0.05) and significantly increased the relative abundance of Bacteroidota (P<0.05). At the genus level, compared with the CON group, the Diquat group significantly decreased the abundance of Lactobacillus and Alistipes (P<0.05), while QG supplementation significantly alleviated the decrease in the abundance of Lactobacillus and Alistipes (P<0.05). In conclusion, the addition of an appropriate amount (20 mg/kg) of QG to the diet can promote the growth of broilers, enhance antioxidant capacity, and improve intestinal health.